2015
DOI: 10.1590/0102-33062015abb0061
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of post-harvest early-developmental categories for viability maintenance of Araucaria angustifolia seeds

Abstract: Araucaria angustifolia seeds are recalcitrant, and their metabolism remains high during storage. This research aimed to describe the initiation of germination in A. angustifolia seeds during storage in order to standardize the assessment of physiological quality and to promote seed conservation. Seeds were collected from two populations and stored for 270 days in the natural laboratory environment and cold chamber. Seeds were classified according to four early developmental stages: I -mature seeds; II -seeds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Among the groups that persist in the area, the panel that was demonstrated up to two decades ago did not change much afterward (Figure 1). The majority of the studies are basically focused on desiccation tolerance Corsato et al, 2012;Chapell et al, 2015;Amoedo and Ferraz, 2017;Gasparin et al, 2017;Subbiah et al, 2017;Chandra and Keshavkant, 2018;Plitta-Michalak et al, 2018), identification of storage behavior (Comin et al, 2014;Joshi et al, 2015;Vicente et al, 2016; 2017; Plitta-Michalak et al, 2018), analysis of deterioration and evaluation of techniques to extend the storage period (Barbedo and Cicero, 2000;Andréo et al, 2006;Bonjovani and Barbedo, 2008;Ballesteros et al, 2014;Lan et al, 2014;Parkhey et al, 2014;Garcia et al, 2015;Ming-Yue et al, 2015;Umarani et al, 2015;Araldi et al, 2016;Hossel et al, 2016;Félix et al, 2017), and rare studying other aspects such as seed maturation (Avila et al, 2009;Lamarca et al, 2013b;Mata et al, 2013;Schultz et al, 2014;Araldi and Coelho, 2015;Shibata and Coelho, 2016;Souza et al, 2018a, b), whose importance will be discussed later, and ecological (Ramlall et al, 2015;Vaz et al, 2016;Porto et al, 2018) or germinative aspects (Moothoo-Padayachie et al, 2016). An analysis, albeit superficial, of studies developed in Brazil and in the world shows small differences.…”
Section: The Research With Recalcitrant Seedsmentioning
confidence: 99%
“…Among the groups that persist in the area, the panel that was demonstrated up to two decades ago did not change much afterward (Figure 1). The majority of the studies are basically focused on desiccation tolerance Corsato et al, 2012;Chapell et al, 2015;Amoedo and Ferraz, 2017;Gasparin et al, 2017;Subbiah et al, 2017;Chandra and Keshavkant, 2018;Plitta-Michalak et al, 2018), identification of storage behavior (Comin et al, 2014;Joshi et al, 2015;Vicente et al, 2016; 2017; Plitta-Michalak et al, 2018), analysis of deterioration and evaluation of techniques to extend the storage period (Barbedo and Cicero, 2000;Andréo et al, 2006;Bonjovani and Barbedo, 2008;Ballesteros et al, 2014;Lan et al, 2014;Parkhey et al, 2014;Garcia et al, 2015;Ming-Yue et al, 2015;Umarani et al, 2015;Araldi et al, 2016;Hossel et al, 2016;Félix et al, 2017), and rare studying other aspects such as seed maturation (Avila et al, 2009;Lamarca et al, 2013b;Mata et al, 2013;Schultz et al, 2014;Araldi and Coelho, 2015;Shibata and Coelho, 2016;Souza et al, 2018a, b), whose importance will be discussed later, and ecological (Ramlall et al, 2015;Vaz et al, 2016;Porto et al, 2018) or germinative aspects (Moothoo-Padayachie et al, 2016). An analysis, albeit superficial, of studies developed in Brazil and in the world shows small differences.…”
Section: The Research With Recalcitrant Seedsmentioning
confidence: 99%
“…Brazilian pine seeds remain metabolically active during storage, and present changes associated with the germination process (Amarante et al, 2007;Araldi & Coelho, 2015a); a characteristic that constitutes the basis of its recalcitrant behavior (Pammenter & Berjak, 2013). In fact, seed germination under storage was observed inside the plastic package.…”
Section: Resultsmentioning
confidence: 99%
“…If the conditions are not ideal for completing the process (as in the case of the seeds that remain stored), deterioration will commence (Pammenter & Berjak, 2013;Walters, 2015). Therefore, Brazilian pine seeds that maintain pre-germinative metabolism for longer can be stored for a longer period (Araldi & Coelho, 2015a). …”
Section: /8mentioning
confidence: 99%
“…However, seeds from local varieties of A. angustifolia showed great diversity of physical and physiological parameters, which may reflect that a relevant genetic diversity is still present (Shibata, Coelho, Araldi, Adan, & Peroni, 2016;Araldi, Coelho, & Shibata, 2018). Its mature seeds are formed by a bulky megagametophyte, the major storage tissue, and an embryo, which represents only 1.3% of the total weight of the seed (Araldi & Coelho, 2015). Starch and protein have been considered the most important reserve compounds in mature seeds of A. angustifolia (Panza, Láinez, Maroder, Prego, & Maldonado, 2002;Balbuena et al, 2011;Araldi, Coelho, & Maraschin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Germination process events, including an increase in the levels of protein synthesis and meristem cell metabolism, initiate shortly after shedding of A. angustifolia seeds and continue during storage (Farrant, Pammenter & Berjak, 1989). Additionally, there is visual evidence of the onset of germination in seeds stored for 30 days inside transparent plastic containers in the natural environment without the supply of additional water (Araldi & Coelho, 2015). These authors suggested that heterogeneity in the degree of seed maturity is an important aspect in determining the storability of A. angustifolia seeds.…”
Section: Introductionmentioning
confidence: 99%